Semi-automated colour registration and evaluation of digital photogrammetry and terrestrial laser scanning - Lim, Kwanthar; Bae, Kwang-Ho; Belton, David (New Zealand Institute of Surveyors and the Surveying and Spatial Sciences Institute, 2011)
Photogrammetry and Laser Scanning fusion is becoming increasingly common. This paper outlines the evaluation and semi-automated registration of single colour image to laser scanning point cloud data using canonical transformation and Direct Linear Transformation (DLT) registration methods. Laser scanning acquires 3D data points and intensity values but is unable to directly obtain photorealistic colour in most cases. There are instances where digital images are taken of the object of interest with the intention to merge the 3D data and image to reconstruct a photorealistic digital representation. Currently limited methods exist for the registration of multisensory platforms; a common method seen requires specially designed camera mounting. Another possibility is to transfer colour information from 2D images to the 3D points using photogrammetric methods.This method was inspired by the SCI method (Forkuo and King, 2005); the registration process utilises synthetic imagery calculated from laser scanning point clouds and matched with a camera image for colour registration. Evaluation is necessary as it provides a metric indication of accuracy and precision. The proposed research intends to aid in heritage and city modelling, to further feature detection methods, to provide cost effectiveness in industrial applications and to potentially improve model visualisation times.